OWA operator based link prediction ensemble for social network. Issue 1 (January 2015) - He, Yu-lin; Liu, James N.K.; Hu, Yan-xing; Wang, Xi-zhao
Highlights This paper firstly studied the link prediction ensemble for local information based algorithms. The integration of individual algorithms is finished via OWA operator. Experimental results reveal the better performances of our proposed link prediction ensemble algorithm.